Characterisation of Vibrio anguillarum for the development of vaccine in cod (Gadus morhua). - Gratacap, Remi M. L. (University of Stirling, 2008)
Atlantic cod (Gadus morhua L.) is one of the most promising new fish species introduced to cold water aquaculture due to the large established market in Europe and the USA and the decline in wild stock. So far, the production of farmed cod has been relatively low, with the main hindrance due to diseases. Vibrio anguillarum has been recognised as the biggest disease problem of farmed cod and has slowed the development of a successful cod aquaculture industry. When the first incidences of V. anguillarum occurred in cod aquaculture, vaccines designed for vibriosis in Atlantic salmon (Salmo salar L.) were used in an attempt to combat the disease. However, these vaccines did not provide sufficient protection, possibly because they lacked serotype O2b, which is known to affect cod and to a lesser extent salmonids. Recently, vibriosis vaccines specifically designed to protect Atlantic cod have been formulated, but outbreaks of vibriosis in vaccinated fish are still being reported, suggesting that these formulations are inadequate. The aim of this project was to develop a whole cell inactivated vaccine formulation specifically tailored to protect Atlantic cod against Vibrio anguillarum. The serological classification of V. anguillarum was first investigated by producing a set of monoclonal antibodies (mAbs). Using lipopolysaccharides (LPS) extracted with butan-1-ol, 4 mAbs were selected and shown to react specifically with V. anguillarum serotypes O1, O2a and O2b. A collection of over 150 V. anguillarum isolates were screened using these, which revealed that most of the isolates had been previously correctly classified. A new sub-serotype of V. anguillarum O2 was identified from isolates recovered from outbreaks of vibriosis in Norway as well as Scotland. This new sub-serotype was referred to as O2d since the subserotype O2c has been recently identified in vibriosis cases from Atlantic cod. However, it was shown that the O2c sub-serotype might not belong to the O2 serotype, but in fact belongs to another serotype. To ...